2016
DOI: 10.1016/j.biopsych.2016.03.1050
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disruption of Circadian Rhythms in the Suprachiasmatic Nucleus Causes Helplessness, Behavioral Despair, and Anxiety-like Behavior in Mice

Abstract: Background Major depressive disorder is associated with disturbed circadian rhythms. To investigate the causal relationship between mood disorders and circadian clock disruption, previous studies in animal models have employed light/dark manipulations, global mutations of clock genes, or brain area lesions. However, light can impact mood by noncircadian mechanisms; clock genes have pleiotropic, clock-independent functions; and brain lesions not only disrupt cellular circadian rhythms but also destroy cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 38 publications
7
123
2
Order By: Relevance
“…Strong evidence is found in recent papers showing that SCN-specific Bmal1 knockdown mice exhibit depression-like behavior (Landgraf et al, 2016) and anhedonic-like behavior is observed in cryptochrome-deficient mice (Savalli et al, 2015). Further, studies have been published investigating the effect of stress on the expression of clock genes in rodents.…”
Section: Discussionmentioning
confidence: 88%
“…Strong evidence is found in recent papers showing that SCN-specific Bmal1 knockdown mice exhibit depression-like behavior (Landgraf et al, 2016) and anhedonic-like behavior is observed in cryptochrome-deficient mice (Savalli et al, 2015). Further, studies have been published investigating the effect of stress on the expression of clock genes in rodents.…”
Section: Discussionmentioning
confidence: 88%
“…Shorter days during winter are associated with seasonal affective disorder and cognitive dysfunction in both humans and nocturnal animals, whereas bright light is an effective therapy for human patients with seasonal or non-seasonal depression 11,13,[79][80][81][82][83][84][85] . Our study showing lightdependent NT plasticity in the SCN-PeVN network is a new mechanism for seasonal adaptation that might prove useful for the development of novel targets and therapeutic approaches for treating seasonal depression and cognitive impairment induced by altered light-dark cycles.…”
Section: Discussionmentioning
confidence: 99%
“…A mutation of casein kinase 1 epsilon specifically in GABAergic neurones results in a lengthened period in constant darkness and reduced body weight at the age of 3‐5 months with no severe metabolic effects . Adeno associated virus‐delivered Bmal1 deletion in the SCN also lengthens the behavioural period, although mutant animals at the same time gain more weight and show altered stress responses . Sf1‐Cre driven clock disruption in the ventromedial hypothalamus was found to reduce body weight in mice, besides comparable food intake, as a result of an increased energy expenditure with a shortened activity period under constant conditions .…”
Section: The Scn Master Clock In Energy Homeostasismentioning
confidence: 97%
“…Bmal1 deletion in the SCN also lengthens the behavioural period, although mutant animals at the same time gain more weight and show altered stress responses 90. Sf1-Cre driven clock disruption in the ventromedial hypothalamus was found to reduce body weight in mice, besides comparable food intake, as a result of an increased energy expenditure with a shortened activity period under constant conditions 91.…”
mentioning
confidence: 99%